Eating chocolate, smelling perfume or watching video advertisement: Does it make any difference on emotional states measured at home using facial expressions?. (October 2019) - Mahieu, Benjamin; Visalli, Michel; Schlich, Pascal; Thomas, Arnaud
Highlights: A home-based protocol of facial expression measurements is feasible. A new method for temporal analyse of facial expressions measurements was developed. Subjects' neutral emotional state was taken into account for temporal analyses. A temporal pattern of implicit emotions was found for perfumes and video advertisements. Ads elicited more implicit emotions than perfumes and chocolates elicited almost none. Abstract: The recording of facial expressions allows for implicit measurement of emotional states over time. The present study investigated whether these recordings can be acquired, using computer webcams, when testing products at home. Three types of product spaces (chocolates, perfumes and video advertisements) were evaluated at home by 44 subjects using a facial expression measurement protocol. Each product space was composed of three products. The first objective examined the feasibility of such a home-based protocol. The second objective investigated whether several products in the same product space could be characterized and discriminated using facial expression measurements. The third objective investigated potential differences in emotional responses between the different types of products. This study showed that a protocol of facial expression measurements at home was feasible and provided conclusive results. Perfumes and video advertisements could be discriminated between them, but chocolates were not discriminated. Perfumes and video advertisements elicited a temporal pattern of implicit emotions. These findings were obtained using a new method for performing a temporal analysis of facial expression measurements that accounts for individual baselines. The strength of the emotional response depended on the product type. Watching video advertisements elicited more emotions than smelling perfumes, which elicited more emotions than eating chocolates. These results showed that facial expression measurements are more adapted to certain product types.